B-Cell Lymphoma 6 (BCL6) Is a Host Restriction Factor That Can Suppress HBV Gene Expression and Modulate Immune Responses - Lin, Chun-Ta; Hsieh, Yue-Ting; Yang, Yeng-Jey; Chen, Shih-Hui; Wu, Cheng-Hsuan; Hwang, Lih-Hwa (Frontiers in Microbiology, 2019)
Hepatitis B virus (HBV) infection causes acute and chronic liver inflammation. Recent studies have demonstrated that some viral antigens can suppress host innate and adaptive immunity, and thus lead to HBV liver persistency. However, the cellular factors that can help host cells to clear HBV during acute infection remain largely unknown. Here, we used HBV-cleared and HBV-persistent mouse models to seek for cellular factors that might participate in HBV clearance. HBV replicon DNA was delivered into the mouse liver by hydrodynamic injection. RNA-Seq analysis was conducted to identify immune-related genes that were differentially expressed in HBV-persistent and HBV-cleared mouse models. A cellular factor, B cell lymphoma 6 (BCL6), was found to be significantly upregulated in the liver of HBV-cleared mice upon HBV clearance. Co-expression of BCL6 and a persistent HBV clone rendered the clone largely cleared, implicating an important role of BCL6 in controlling HBV clearance. Mechanistic studies demonstrated that BCL6 functioned as a repressor, directly binding to and suppressing the activities of the four HBV promoters. Correspondingly, BCL6 expression significantly reduced the levels of HBV viral RNA, DNA and proteins. BCL6 expression could be stimulated by inflammatory cytokines such as TNF-α; the BCL6 in turn synergized TNF-α signaling to produce large amounts of CXCL9 and CXCL10, leading to increased infiltrating immune cells and elevated cytokine levels in the liver. Thus, positive feedback loops on BCL6 expression and immune responses could be produced. Together, our results demonstrate that BCL6 is a novel host restriction factor that exerts both anti-HBV and immunomodulatory activities. Induction of BCL6 in the liver may ultimately assist host immune responses to clear HBV.